A role for glia maturation factor dependent activation of mast cells and microglia in MPTP induced dopamine loss and behavioural deficits in mice - Selvakumar, Govindhasamy Pushpavathi (Brain Behav Immun, 2020)
The molecular mechanism mediating degeneration of nigrostriatal dopaminergic neurons in Parkinson’s disease (PD) is not yet fully understood. Previously, we have shown the contribution of glia maturation factor (GMF), a proinflammatory protein in dopaminergic neurodegeneration mediated by activation of mast cells (MCs). In this study, methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced nigrostriatal neurodegeneration and astro-glial activations were determined by western blot and immunofluorescence techniques in wild type (WT) mice, MC-deficient (MC-KO) mice and GMF-deficient (GMF-KO) mice, with or without MC reconstitution before MPTP administration. We show that GMF-KO in the MCs reduces the synergistic effects of MC and Calpain1 (calcium-activated cysteine protease enzyme)-dependent dopaminergic neuronal loss that reduces motor behavioral impairments in MPTP-treated mouse. Administration of MPTP increase in calpain-mediated proteolysis in nigral dopaminergic neurons further resulting in motor decline in mice. We found that MPTP administered WT mice exhibits oxidative stress due to significant increases in the levels of malondialdehyde, superoxide dismutase and reduction in the levels of reduced glutathione and glutathione peroxidase activity as compared with both MC-KO and GMF-KO mice. The number of TH-positive neurons in the ventral tegmental area, substantia nigra and the fibers in the striatum were significantly reduced while granulocyte macrophage colony-stimulating factor (GM-CSF), MC-Tryptase, GFAP, IBA1, Calpain1 and intracellular adhesion molecule 1 expression were significantly increased in WT mice. Similarly, tyrosine hydroxylase, dopamine transporters and vesicular monoamine transporters 2 proteins expression were significantly reduced in the SN of MPTP treated WT mice. The motor behavior as analyzed by rotarod and hang test was significantly reduced in WT mice as compared with both the MC-KO and GMF-KO mice. We conclude that GMF-dependent MC activation enhances the detrimental effect of astro-glial activation-mediated oxidative stress and neuroinflammation in the midbrain, and its inhibition may slowdown the progression of PD.